Holistic classification of CT attenuation patterns for interstitial lung diseases via deep convolutional neural networks - Gao, Mingchen; Bagci, Ulas; Lu, Le; Wu, Aaron; Buty, Mario; Shin, Hoo-Chang; Roth, Holger; Papadakis, Georgios Z.; Depeursinge, Adrien; Summers, Ronald M.; Xu, Ziyue; Mollura, Daniel J. (Computer methods in biomechanics and biomedical engineering., 2018)
Interstitial lung diseases (ILD) involve several abnormal imaging patterns observed in computed tomography (CT) images. Accurate classification of these patterns plays a significant role in precise clinical decision making of the extent and nature of the diseases. Therefore, it is important for developing automated pulmonary computer-aided detection systems. Conventionally, this task relies on experts' manual identification of regions of interest (ROIs) as a prerequisite to diagnose potential diseases. This protocol is time consuming and inhibits fully automatic assessment. In this paper, we present a new method to classify ILD imaging patterns on CT images. The main difference is that the proposed algorithm uses the entire image as a holistic input. By circumventing the prerequisite of manual input ROIs, our problem set-up is significantly more difficult than previous work but can better address the clinical workflow. Qualitative and quantitative results using a publicly available ILD database demonstrate state-of-the-art classification accuracy under the patch-based classification and shows the potential of predicting the ILD type using holistic image.